Briquettes produced with differents granulometries for sugarcane bagasse and straw mixtures - Delfino, Bruna Monise; Corrêa, Plínio Magalhães; Sinohara, Rafael Yassuo; Yamaji, Fábio Minoru; Conti, Andrea Cressoni De (Revista Hipótese, 2018)
This paper proposes the study and use of sugarcane biomass for the preparation and analysis of briquettes. The immediate chemical analysis, apparent density and calorific value analysis for the bagasse and straw mixture were performed. The volumetric expansion of 12 briquettes with 20 mesh and 12 with 40 mesh granulometry was analyzed. Biomass was prone to energy generation. Greater union with smaller particles was observed, making the volumetric expansion of the 40 mesh briquette more stable.